2020
DOI: 10.1039/d0ce00440e
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new polymorphs of the tuberculosis drug isoniazid

Abstract: Two new metastable polymorphs of the tuberculosis drug isoniazid, considered monomorphic for sixty years, were discovered using melt crystallization and nanoscale confinement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 36 publications
6
46
0
Order By: Relevance
“…Despite isoniazid in the pure state being stable for long periods of time, when administrated with other anti-tuberculosis drugs, it interacts and becomes unstable and suffers some degradation. Recently, it was reported that two polymorphs that are formed by hydrogen bonding in pyridine group (N-H…N) and another one in hydrazide groups (N-H…O) [ 35 ]. This anti-tuberculosis drug may be sensitive to light, when exposed for long periods of time, and is an active substance that, usually, is vulnerable to hydrolysis, oxidation, and interaction with other compounds (e.g., excipients used in formulation) to form hydrazones [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite isoniazid in the pure state being stable for long periods of time, when administrated with other anti-tuberculosis drugs, it interacts and becomes unstable and suffers some degradation. Recently, it was reported that two polymorphs that are formed by hydrogen bonding in pyridine group (N-H…N) and another one in hydrazide groups (N-H…O) [ 35 ]. This anti-tuberculosis drug may be sensitive to light, when exposed for long periods of time, and is an active substance that, usually, is vulnerable to hydrolysis, oxidation, and interaction with other compounds (e.g., excipients used in formulation) to form hydrazones [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, a new strategy for synthesis of organic salts using isoniazid drug as cation and combined with sulfonate and carboxylate counterions was explored. This new approach for the synthesis of API-OSILS with the isoniazid drug has the main goal of stabilizing this drug and avoiding polymorphic forms [ 35 ] and to understand if its properties could be tuned by the protonation of isoniazid with biocompatible counterions. The counterions selected to be combined with isoniazid were chosen as they are generally considered biocompatible and are commercially available [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We note that, during the preparation of this article, a new study reporting the discovery of two new metastable polymorphs of IZN has also been published. 29 The remaining hits are made up of 41 different MC materials. Of these, the vast majority of API-co-former interactions involved N⋯OH or N⋯COOH hydrogen bonds between the pyridine nitrogen atom on IZN and the coformer.…”
Section: Workflow Inputs/prerequisitesmentioning
confidence: 99%
“…Until very recently, isoniazid (ISN) was thought to be monomorphic, 15 but despite the molecule being known for almost 70 years, two new forms were recently discovered by via crystallization from the melt. 16 The most famous case of late-appearing polymorphism is that of ritonavir, an antiretroviral drug synthesized by Abbott Laboratories with a late-appearing polymorph that resulted in a two-year halt in production and $250 million in lost sales. 1,17,18 Bučar et al have discussed 10 other cases of elusive or disappearing polymorphs.…”
Section: The Significance Of Late-appearing Polymorphismmentioning
confidence: 99%
“…In this work, we combine computational CSP with both traditional and non-traditional experimental crystallization approaches to explore the polymorphism of two related molecules, ISN and iproniazid (IPN). Until very recently, 16 ISN was thought to have a single obtainable nonsolvated structure, although it forms a number of cocrystals. 36 The recent work of Zhang et al 16 has located two additional, metastable forms (Forms II and III) of ISN via crystallization from the melt.…”
Section: Rationalizing Polymorph Risk Through Computed Energeticsmentioning
confidence: 99%